Model Kausalitas Purchase Intention Online Produk X: Social Media Marketing, Online Review, Price Discount dan Halal Cosmethic - Siti Holipah; Ryna Parlyna; Fildzah Shabrina (Indo Publishing, 2026)
This study was conducted to examine the causal relationship between social media marketing, online reviews, price discounts, and halal cosmetics on consumer purchase intention for skincare product X in the digital environment. The approach used was quantitative, using the Partial Least Square Structural Equation Modeling (PLS-SEM) method, analyzed using SmartPLS software. The study involved 170 respondents aged 18–28 who actively access skincare products through digital media. Respondents were selected using a purposive sampling technique, while the research instrument consisted of 17 statement items. The study findings indicate that social media marketing, online reviews, and halal cosmetics have a positive and significant influence on purchase intention, while price discounts did not prove to have a significant effect. Practically, the results of this study were implemented through the development of a prototype e-commerce skincare application called SKINSHOP, designed as a decision support system to assist consumers in selecting skincare products more systematically and informatively.